2006
DOI: 10.4103/0255-0857.29388
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and microbiological correlates of premature rupture of membranes

Abstract: Prematurity is the cause of 85% of neonatal morbidity and mortality. Premature rupture of the membranes (PROM) is associated with 30-40% of preterm deliveries. A case-control study conducted between July 2002 and 2003 examined the correlates and risk factors for PROM in Mysore, India. WBCs in vaginal fluid, leucocytes in urine, UTI and infection with E. coli, S. aureus, C. albicans and BV were significantly associated with PROM. BV, E. coli and WBCs in vaginal fluid were independent risk factors. Screening and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 11 publications
4
23
0
2
Order By: Relevance
“…Karat et al reported S aureus (28%) and E coli (20%) as significant vaginal isolates in-patient with PPROM. 7 Carroll et al reported that positive genital tract cultures for aerobic and anaerobic organisms predicted 40% of positive fetal blood and 53% of positive amniotic fluid cultures. In more than 75% of cases with positive amniotic fluid cultures, the same organisms were recovered from high vaginal swabs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Karat et al reported S aureus (28%) and E coli (20%) as significant vaginal isolates in-patient with PPROM. 7 Carroll et al reported that positive genital tract cultures for aerobic and anaerobic organisms predicted 40% of positive fetal blood and 53% of positive amniotic fluid cultures. In more than 75% of cases with positive amniotic fluid cultures, the same organisms were recovered from high vaginal swabs.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is only one previous study from India, which reported microbiological correlates of PPROM. 7 Antibiotic therapy in PPROM has been associated with significant reduction in incidence of chorioamnionitis, birth within one week of starting antibiotics and improved neonatal outcomes. Due to difficulty in obtaining amniotic fluid samples and various reports indicating mixed bacterial growth in amniotic fluid cultures, broad-spectrum antibiotics are prescribed during expectant management of PPROM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less than 37 weeks of gestation, first trimester infection and BV were the risk factors we found to be associated with PROM [13] . These results were unlikely to be due to sample selection bias or by chance.…”
Section: Discussionmentioning
confidence: 56%
“…PROM is reportedly associated with many risk factors, including trauma and cervical tubal relaxation, a mechanical irritation occurring in late pregnancy, fetal meningitis, lower reproductive tract infections, an increase in amniotic pressure (such as in multiple pregnancies and polyhydramnios) [12][13][14] , a history of PROM in a previous pregnancy and BMI ! 20 [12] .…”
mentioning
confidence: 99%